Substitution of potassium by sodium in sugar beet (Beta vulgaris L.) : Nutrition with special reference to K-fixing soils - Wakeel, Abdul; Justus Liebig University Giessen (My University, 2008)
Plant growth does not response to the application of generally recommended levels ofpotassium (K) fertilizer in the soils with expandable three layer clay minerals. In the soilsrich in illite and vermiculite clay minerals with high cation exchange capacity, a major partof applied K is fixed and becomes unavailable to plants immediately.It is known that several members of the family Chenopodiaceae such as sugar beet,spinach, red beet etc. are capable to use sodium (Na) as an osmoticum for which 95% oftotal acquired K is required. We hypothesized that Na is able to substitute K to a largeextent in sugar beet nutrition without affecting the plant growth and beet quality. Weassumed that in K-fixing soils it would be possible to replace a huge amount of K fertilizerwith adequate amount of Na fertilizer, which may lead to the development of an interestingfertilizer strategy for sugar beet in K-fixing soils. In this study, an attempt was made toidentify the limiting processes when K was substituted by Na in K-fixing soils.Three soil and two nutrient solution experiments were conducted to test the abovementionedhypothesis. In the first soil experiment, soils from three locations (i.e.Kleinlinden, Giessen and Trebur) with different K-fixing capacity were tested and sugarbeet plants were grown in Ahr pots under natural climatic conditions (April 2005 toSeptember 2005, Giessen, Germany) and harvested at maturity. Three treatments wereused i.e. control (no K and Na fertilizer), potassium treatment (K2SO4 fertilizer wasapplied according to K-fixing capacity of soil) and in third treatment NaCl was appliedequivalent to regular K fertilization. Soil Kleinlinden was tested again in anotherexperiment where sugar beet plants were grown in containers (169 kg soil container-1) withthe same treatments as in the previous Ahr pot experiment, except potassium treatment.Potassium was not applied according to K-fixing capacity of soil, rather according toregular K fertilization. A field experiment was conducted on the Trebur soil (similar to thesoil used in the Ahr pot experiment). The treatments were the same as in the containerexperiment; nevertheless an extra treatment was used where a huge amount (i.e. equivalentto half K-fixing capacity of the soil) of K was applied. The results of all the experimentsrevealed that application of Na fertilizer significantly improved the plant growth relative tothe control. However, white sugar yield in Na treatment was similar to that in K treatment.Moreover, Na eliminated the K deficiency symptoms in the plant leaves, but application ofNa fertilizer decreased the calcium (Ca) concentration in the expanding leaves due toreduced Ca uptake and Ca translocation from root to shoot, which was investigated innutrient solution experiments with Na and K treatments.Despite many fruitful findings from the earlier studies on Na nutrition of plants, inpractical agriculture Na is not used as a nutrient. We conclude that Na may substitute K toa large extent in sugar beet nutrition without affecting the plant growth and beet quality,and soils with higher K-fixing capacity and illite and/or vermiculite clay minerals are morefavorable for this substitution.

Es wurde beobachtet, dass die allgemein empfohlene Applikation von K-Düngemitteldas Pflanzenwachstum in Böden mit aufgeweiteten Dreischicht-Tonmineralen nichtbeeinflusst. Die Böden, reich an den Tonmineralen Illit und Vermiculit haben einehohe CEC und der größte Teil des gedüngten K wurde fixiert, sodass es für diePflanzen nicht verfügbar war.Es ist bekannt, dass viele Arten der Familie der Chenopodiaceae, wie Zuckerrübe,Spinat, Rote Beete, etc. in der Lage sind, Na als Osmoticum zu verwenden hierfürwerden ansonsten 95% des aufgenommenen K benötigt. Ziel unserer Untersuchungenwar es herauszufinden, ob Na in der Lage ist, K in der Ernährung von Zuckerrüben zuersetzen, ohne das Pflanzenwachstum oder die Rübenqualität zu beeinflussen. DesWeiteren wurde überlegt, ob in K-fixierenden Böden ein großer Anteil des K-Düngersdurch Na-Dünger ersetzt werden kann, was zu einer interessanten Düngerstrategie fürZuckerrüben führen könnte. Zunächst wurden die limitierenden Einflüsse erforscht,die auftreten, wenn K durch Na ersetzt wird.Drei Boden- und zwei Nährlösungsversuche wurden zur Überprüfung der Hypothesedurchgeführt. Für den ersten Bodenversuch wurden drei verschiedene Böden (KleinLinden, Gießen und Trebur) mit unterschiedlicher K-Fixierungskapazität verwendet.Die Zuckerrüben wuchsen in Ahrgefäßen bei natürlicher Witterung (April 2005 bisSeptember 2005, Gießen, Deutschland) und wurden zur Reife geerntet. Drei Variantenwurden getestet, eine Kontrollvariante (kein K- und Na-Dünger), eine Kaliumvariante(K2SO4-Applikation in Übereinstimmung mit der K-Fixierungskapazität) und eineNatriumvariante (NaCl entsprechend einer normalen K-Düngung). Ein weiteresExperiment wurde mit Kleinlindener Boden angelegt. Hier wurden die Zuckerrüben inContainern (169 kg Boden Container-1) unter den gleichen Bedingungen und Variantenmit Ausnahme der Kaliumvariante angezogen. Hierzu wurde K in praxisüblicherMenge dazugegeben. Ebenso wurde ein Feldversuch in Trebur auf dem gleichenBoden wie in den Ahrgefäßen durchgeführt. Die Varianten waren die gleichen wie imContainerversuch, allerdings mit einer zusätzlichen Variante, die eine enorme Mengean K gedüngt bekam (entsprechend der halben K-Fixierungskapazität). Die Ergebnissevon aller Versuchen zeigen, dass eine Na-Düngung das Pflanzenwachstum relativ zu-Kontrolle signifikant erhöht, jedoch der Zuckerertrag der gleiche ist, wie in derKaliumvariante. Darüber hinaus konnte Na die K-Mangelsymptome an Blätternverhindern; dennoch wurde die Ca-Konzentration vor allem in wachsenden Blätternbeeinflusst. Daher wurde, ein Nährlösungsversuch in einer Klimakammer mitkontrollierten Bedingungen angelegt. Es zeigte sich, dass durch das Ersetzen von Kdurch Na die Ca-Konzentration im Spross signifikant verringert wurde ohne dasWachstum der Pflanzen zu stören. Die Ca-Aufnahme und Ca-Translokation imXylemsaft waren als Folge der Substitution ebenfalls reduziert.Bisher wird in der praktischen Landwirtschaft Na nicht als Pflanzennährstoffverwendet. Abschließend stellen wir fest, dass Na fähig ist, K in der Ernährung vonZuckerrüben zu ersetzen, ohne dass das Wachstum der Pflanze oder die Qualitätbeeinflusst wird. Böden mit einer hohen K-Fixierungskapazität und einem hohenAnteil an Illit bzw. Vermiculit eignen sich besser für diese Substitution.
Keywords: ddc:630